Penerimaan Diri pada Penyandang Disabilitas Netra di SLB Negeri A Pajajaran Kota Bandung. - ardelia, syahda; Yuningsih, Yuyun (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2024)
The purpose of this study was to describe self-acceptance in blind adolescents aged 12-24 years equivalent to high school. Given that many negative views of society towards blind adolescents make them have low self-acceptance and find it difficult to interact, communicate and participate in activities in the social environment. This study uses a qualitative research method and informant selection techniques with purposive sampling techniques. The data collection techniques used are (1) Observation, (2) In-depth interviews and (3) Document studies. The number of informants, namely key informants consisting of 3, namely blind students with grade 11 high school and 3 secondary informants, namely Guidance and Counseling teachers, Homeroom teachers and OMSK skills teachers. The results of this study, the researcher found information related to the existence of different self-acceptance felt by blind people with accidents and blind people with birth disabilities. Blind people with birth disabilities have good self-acceptance and self-confidence, while blind people with accidents tend to have low self-acceptance because they have experience in sight. In the process of self-acceptance, there are many obstacles that come from the environment or from the blind person themselves.